2018
DOI: 10.3390/ijms19103127
|View full text |Cite
|
Sign up to set email alerts
|

Emodin Sensitizes Hepatocellular Carcinoma Cells to the Anti-Cancer Effect of Sorafenib through Suppression of Cholesterol Metabolism

Abstract: Reduced therapeutic efficacy of sorafenib, a first-generation multikinase inhibitor, is often observed during the treatment of advanced hepatocellular carcinoma (HCC). Emodin is an active component of Chinese herbs, and is effective against leukemia, lung cancer, colon cancer, pancreatic cancer, and HCC; however, the sensitizing effect of emodin on sorafenib-based HCC therapy has not been evaluated. Here, we demonstrate that emodin significantly improved the anti-cancer effect of sorafenib in HCC cells, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 47 publications
1
92
0
Order By: Relevance
“…To measure mRNA expression, quantitative real-time PCR was performed as described previously [ 51 ]. Briefly, total RNA was isolated from cultured cells by using TRIzol reagent (Invitrogen, Carlsbad, CA, USA) and 2 μg of total RNA was used for cDNA synthesis by using a high-capacity cDNA reverse transcription kit (Applied Biosystems, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure mRNA expression, quantitative real-time PCR was performed as described previously [ 51 ]. Briefly, total RNA was isolated from cultured cells by using TRIzol reagent (Invitrogen, Carlsbad, CA, USA) and 2 μg of total RNA was used for cDNA synthesis by using a high-capacity cDNA reverse transcription kit (Applied Biosystems, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The apoptotic cell population was measured by using Muse™ Annexin V and Dead Cell kit (Millipore, Burlington, MA, USA) in accordance with a previously described [51]. Initially, LEF1 stably overexpressing A375 and A2058 cells were generated with puromycin selection.…”
Section: Apoptosis Assaysmentioning
confidence: 99%
“…Natural drugs combined with traditional anti-tumor drugs to increase the sensitivity of cells to treatment are very promising. In the treatment of hepatocellular carcinoma, emodin has been used to increase the sensitivity of cells to sorafenib by regulating SREBP-2 (150). Although the evidence is promising, further research studies are warranted to investigate the mechanism of SREBPs involved in drug resistance.…”
Section: Provide Protection For Tumor Cellsmentioning
confidence: 99%
“…26 Pharmacological researches show that emodin not only has various pharmacological effects such as antibacterial and fungal infections, anti-inflammatory, antioxidant, anti-allergic, etc, but also can regulate the expression of various cancer-related proteins such as Akt/mTOR, NF-κB, HIF1α, and STAT3 to achieve the effects of inhibiting cell proliferation and migration, promoting cell apoptosis, and inhibiting multidrug resistance in a variety of malignant tumors. 23,27,28 In 2013, Zhang et al 29 found that the combined use of emodin and gemcitabine significantly reduced the expression of NF-κB, XIAP and survivin in pancreatic cancer cells, thereby making BxPC-3 cells that were originally resistant to gemcitabine have…”
Section: Discussionmentioning
confidence: 99%